1997
DOI: 10.1002/(sici)1097-0142(19970115)79:2<320::aid-cncr15>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Progestin alone as primary treatment of endometrial carcinoma in premenopausal women

Abstract: The results of this study show that premenopausal women with endometrial carcinoma may be treated successfully with progestin therapy alone as primary therapy to preserve childbearing potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0
11

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(152 citation statements)
references
References 27 publications
3
138
0
11
Order By: Relevance
“…Some small series have been reported in which grade 1, stage 1 ECs have been successfully treated with progestins alone (for reviews see Kim et al 1997, Randall & Kurman 1997, Quinn 1999. A response rate of 66% has been calculated and 11 pregnancies (two after in vitro fertilization) have been reported (Paulson et al 1990, Kim et al 1997, Randall & Kurman 1997, Zuckerman et al 1998.…”
Section: Primary Treatment Of Early Ec With Progestinsmentioning
confidence: 99%
“…Some small series have been reported in which grade 1, stage 1 ECs have been successfully treated with progestins alone (for reviews see Kim et al 1997, Randall & Kurman 1997, Quinn 1999. A response rate of 66% has been calculated and 11 pregnancies (two after in vitro fertilization) have been reported (Paulson et al 1990, Kim et al 1997, Randall & Kurman 1997, Zuckerman et al 1998.…”
Section: Primary Treatment Of Early Ec With Progestinsmentioning
confidence: 99%
“…Studies at various institutions have reported the results of fertility-sparing treatment for EC using progesterone preparations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, as the number of cases have been low, the efficacy of such treatment has yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…To summarize the domestic and overseas reports on progestin therapy applied as fertility-preserving therapy in 1997 through 2008, the lesions disappeared in 164 (75%) of the 218 cases of endometrial cancer (corresponding to G1 endometrioid adenocarcinoma, FIGO 1988 surgical stage Ia) in response to progestin therapy. Among these 164 cases showing disappearance of lesions, recurrence was later noted in 53 (36%) of the 148 cases where information on the presence/absence of recurrence was available (Table I) (14,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). When progestin therapy was applied to 47 cases of atypical endometrial hyperplasia, 42 cases (89%) showed disappearance of lesions, and 8 (19%) of these 42 cases later showed recurrence (Table II) (26,27,31,35).…”
Section: Progestin Therapy For Endometrial Cancermentioning
confidence: 99%
“…Among these 164 cases showing disappearance of lesions, recurrence was later noted in 53 (36%) of the 148 cases where information on the presence/absence of recurrence was available (Table I) (14,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). When progestin therapy was applied to 47 cases of atypical endometrial hyperplasia, 42 cases (89%) showed disappearance of lesions, and 8 (19%) of these 42 cases later showed recurrence (Table II) (26,27,31,35). Regarding the efficacy of progestin therapy on endometrial cancer, Montz et al reported that when progestin therapy was administered to cases of G1 endometrial cancer (FIGO 1988 surgical stage Ia) not indicated for surgery for reasons of influence of complications or preservation of fertility, the tumor was histologically rated as negative in 7 of the 11 cases at 6 months and 6 of the 8 cases at 12 months after the start of treatment (36).…”
Section: Progestin Therapy For Endometrial Cancermentioning
confidence: 99%